İLKÖĞRETİM ÖĞRENCİLERİNİN GÖRÜŞLERİNE GÖRE ÖĞRETMENLERİN ETKİLİLİĞİ - Erten GÖKÇE (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The primary aim of this study was to determine teachers’ efficiency in the light of elementary school students’ views. The study group of this research consists of 426 elementary school students in Elementary Schools in Ankara chosen for ‘teaching practice’. The data were collected in May, 2002. the data were gathered from the third and fifth year elementary school students. Frequency and percentage methods were employed to analyse the study. According to the results of the study, it was concluded that the teachers gave enough examples to illustrate their point of view, they asked questions related to the subjects they taught, they were tolerant, and in good intention. However, they did not give enough importance to games, discussion activities, group studies which can serve to help them to become active participants. Furthermore, the results demonstrated that the teachers did not move around in class and they did not create equal opportunity for the students to participate. Moreover, it came into the light that parents did not participate in school activities sufficiently. A majority of students saw their students successful, and added that a successful and efficient teacher should have such characteristics as love for children, being patient and tolerant, treating everybody equally and having a smiling face. In this study some suggestions were made to make teaching-learning process more efficient and effective, and some suggestions were also given to live up to students expectations